A new species of Plesiogulo (Mustelidae: Carnivora) from the Late Miocene of Africa - Haile-Selassie, Yohannes; Hlusko, Leslea J; Clark Howell, F (Bernard Price Institute for Palaeontological Research, 2004)
A new species of Plesiogulo (Plesiogulo botori sp. nov.) is described from 5.5–6.0 Ma deposits in East Africa. This new fossil material comes from two localities: Lemudong’o in southern Kenya, and Adu Dora, in the Afar Depression of Ethiopia. The new mustelid species is larger than all known OldWorld Plesiogulo species and extends the temporal and spatial range of the genus inAfrica. Plesiogulo botori sp. nov. documents the earliest occurrence of the genus in Africa in general and the first evidence of its occurrence in late Miocene deposits of eastern Africa. Associated mammalian fauna at both localities where the species has been found indicate a closed/wooded habitat for the genus. This and other occurrences of the genus across Europe, Asia, and the New World indicate that the genus Plesiogulo was geographically widely dispersed during the upper Tertiary.
Keywords: Late Miocene, Carnivora, Mustelidae, Kenya, Ethiopia.